2013
DOI: 10.1080/10401334.2012.741535
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students Ultrasound to Measure Liver Size: Comparison With Experienced Clinicians Using Physical Examination Alone

Abstract: With limited instruction and clinical experience medical students can obtain liver size measurements with ultrasound that are more accurate and have less variability than those by physicians using physical examination. Given the ease with which students can learn to use ultrasound and the teaching and clinical value of ultrasound, ultrasound should be considered as a standard of medical education in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 14 publications
0
73
0
Order By: Relevance
“…Senior medical students, whose learning objectives have graduated to the diagnosing of disease in real-world patients, have demonstrated significant improvement in their ability to diagnose disease following brief, focused ultrasound teaching programs [64][65][66][67][68]. These benefits are particularly impressive when benchmarked against postgraduate medical practitioners using either physical examination [69,70] or ultrasound [71,72]. The obstetric ultrasound study of Hamza et al is notable for its use German Society of Ultrasound in Medicine (DEGUM) guidelines as the source material for student teaching, and for its use of a standardised teaching approach [73].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 90%
“…Senior medical students, whose learning objectives have graduated to the diagnosing of disease in real-world patients, have demonstrated significant improvement in their ability to diagnose disease following brief, focused ultrasound teaching programs [64][65][66][67][68]. These benefits are particularly impressive when benchmarked against postgraduate medical practitioners using either physical examination [69,70] or ultrasound [71,72]. The obstetric ultrasound study of Hamza et al is notable for its use German Society of Ultrasound in Medicine (DEGUM) guidelines as the source material for student teaching, and for its use of a standardised teaching approach [73].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 90%
“…Recent studies have described POCUS as being easily taught to medical personnel with a high degree of accuracy [1,9,10]. Medical schools have integrated ultrasound into their teaching curriculum, and students are using it from basic anatomy to advanced imaging as an adjunct to diagnosis and physical examination [11,12]. The use of POCUS in the pre-hospital setting is also increasing as an aid to early diagnosis and medical decision-making [13].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It can improve physical examination findings and diagnostic accuracy, and result in potential changes to management. [4][5][6] Prior studies have shown that ultrasound knowledge and skill can be acquired through dedicated training. 7,8 Various specialties, such as anesthesia, 9 orthopedics, 10 and emergency medicine, 11 have implemented formal ultrasound training.…”
Section: Introductionmentioning
confidence: 99%